Analisis Perbandingan Antara Perumahan Subsidi dengan Perumahan Green Building - Widya Wardani, Tri; Syahara, Syahara; Terkelin, Windu; Indira, Sri Shindi; Nuraini, Cut (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2024)
This study compares subsidized housing with Green Building housing based on cost, energy efficiency, occupant quality of life, and environmental impact. The government supports subsidized housing to provide affordable housing for low-income people, although the initial cost is low and often has ordinary building quality standards and higher operating costs. On the other hand, Green Building housing emphasizes sustainability by providing better energy efficiency, more efficient use of resources, and a healthier living environment. However, it requires a higher initial investment. The results of the analysis show that although subsidized housing is more economical at the beginning, Green Building provides significant long-term benefits in terms of energy and water savings and improves occupants' quality of life. Combining Green Building elements in subsidized housing development is recommended to improve the quality and sustainability of housing for low-income people. This study concludes that a hybrid approach integrating Green Building principles in a subsidized housing development can effectively solve housing and environmental challenges